2022
DOI: 10.5334/tohm.695
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Drug-induced Movement Disorders with Newer Antipsychotic Agents

Abstract: Background: The last decade has seen development of numerous novel antipsychotic drugs with unique mechanisms including long-acting formulations for clinical use. A comparative assessment of these new drugs with each other and previous antipsychotics have not been performed with regards to risk for drug-induced movement disorders (DIMD). Methods: Medline was searched from January 2010 to February 2022 for primary research articles and review articles in English using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 149 publications
0
6
0
Order By: Relevance
“…Interestingly, in our case, there is a lack most of the risk factors, with the exception of the early appearance of akathisia. Although cariprazine has comparable rates of drug-induced movement disorders relative to previous SGAs, it may be more prone to causing akathisia, particularly early in treatment, relative to aripiprazole and risperidone 17 . Akathisia constitutes a risk factor for later development of TD; this seems to be relevant in our case, where our patient developed akathisia early in treatment along with an early onset of TD symptoms.…”
Section: Discussionmentioning
confidence: 68%
“…Interestingly, in our case, there is a lack most of the risk factors, with the exception of the early appearance of akathisia. Although cariprazine has comparable rates of drug-induced movement disorders relative to previous SGAs, it may be more prone to causing akathisia, particularly early in treatment, relative to aripiprazole and risperidone 17 . Akathisia constitutes a risk factor for later development of TD; this seems to be relevant in our case, where our patient developed akathisia early in treatment along with an early onset of TD symptoms.…”
Section: Discussionmentioning
confidence: 68%
“…However, one of the significant side effects associated with these medications is the development of movement disorders, known as antipsychotic-induced movement disorders (AIMDs). These AIMDs can range from acute and reversible to chronic and irreversible conditions, posing significant challenges in the management of patients receiving antipsychotic treatment [24].…”
Section: Antipsychotic Medicationsmentioning
confidence: 99%
“…69,77 The relative risk of long-acting injectable antipsychotics compared to oral agents is unclear but likely similar, with newer SGAs less likely than FGAs to cause TD in some but not all studies. [78][79][80][81] Studies of long-acting injectable agents have suggested that guaranteed continuous administration of antipsychotics may actually decrease the risk of TD compared with intermittent treatment resulting from "drug holidays," symptom-driven administration or patient nonadherence. [82][83][84][85] The effect of other prescription drugs or substance abuse on the risk of TD is less clear.…”
Section: Risk Factorsmentioning
confidence: 99%
“…In addition, research and development of antipsychotics that target novel brain targets (trace amine-associated receptor 1 agonists, serotonin agonists and serotonin/opioid antagonists, muscarinic receptor agonists) that lack dopamine receptor affinity may offer promise as effective antipsychotics without movement disorder liability. 78 Meanwhile, VMAT2 inhibitors are likely to transform the treatment of TD and renew interest in TD research. 172 Although trials of VMAT2 inhibitors offer clear evidence of efficacy and tolerability in suppressing TD, their impact on real-world outcomes merits additional investigation.…”
Section: Formulating Individualized Treatment Plans For Patients With...mentioning
confidence: 99%
See 1 more Smart Citation